An evaluation of the effectiveness of countermeasures for improving the safety of dilemma zones: A driving simulator study. (May 2022) - Calvi, Alessandro; Petrella, Claudio
Highlights: Dilemma zone significantly affects the safety of signalized intersection. Several countermeasures have been tested for tackling the dilemma zone using a driving simulator. Warnings to drivers at the start of the yellow signal helps drivers in taking safer decisions. Augmented Reality and connected vehicle technologies improve signalized intersection safety. Abstract: The main objective of this driving simulator study is to analyze the behavior of the driver at the start of the yellow signal of a signalized rural intersection and identify the most effective countermeasures for tackling the dilemma zone, namely an area on the intersection approach where vehicles at the start of the yellow phase can neither safely stop before the stop line nor cross the intersection. The following countermeasures were tested in the study on a sample of 48 drivers: green signal countdown timers, GSCT (C1 ); a new pattern of vertical and horizontal warning signs (C2 ); and an advanced on-board driver assistance system based on augmented reality (AR) and connected vehicle technologies (C3 ). These countermeasures were tested and compared to a baseline condition (B) where no countermeasures were applied. Based on the results of this study, the C2 and C3 countermeasures have proven to be valid tools for reducing driver indecision when approaching signalized intersections at the start of the yellow signal. In fact, using C2 and C3, the length of the dilemma zone was equal to 30 m and 36 m, respectively, with a reduction of about 50%, as compared to the baseline condition (B). Moreover, a reduced number of false behaviors was recorded, as well as a greater consistency in driver decision-making behaviors. Conversely, the C1 countermeasure did not lead to a significant improvement in the dilemma zone: an unnecessary increase in early stop rates was recorded, resulting in reduced intersection efficiency and operations.